Use of visual feedback during jump-squat training aids improvement in sport-specific tests in athletes - Vanderka, M.; Bezák, A.; Longová, K.; Krcmár, M.; Walker, S. (The Journal of Strength and Conditioning Research, 2020)
This study investigated the effects of instantaneous performance feedback during the jump-squat exercise over a 6-week training period. Twenty-five strength-trained athletes were randomly divided into an instant feedback (n = 13, half-squat 3-repetition maximum (3RM)/body mass = 2.38 ± 0.19) or a nonfeedback (n = 12, half-squat 3RM/body mass = 2.03 ± 0.44) group. Both groups performed the same training program (3 × week), consisting of 4 sets of 8 repetitions (weeks 1-3) and 8 sets of 4 repetitions (weeks 4-6) using a barbell with a load that maximized the average concentric power output (Pmax) of each athlete. Subjects in the instant feedback group were given real-time data after each repetition. Pre-, mid-, and post-training testing consisted of maximum 20-, 30-, and 50-m running speed, 3RM back half-squat load, Pmax and the load that maximized average concentric power output (Pmax load), countermovement jump (CMJ), and squat jump (SJ) height. Results revealed that the feedback group significantly improved all selected tests vs. nonfeedback (time × group interaction, p < 0.01). Significant improvements after training for 20, 30, 50 m, 3RM load, Pmax load, CMJ, and SJ were observed in the feedback group only (p < 0.01). Training without instant feedback did not lead to significant performance improvements; this group actually demonstrated significant decreases in SJ and Pmax (W) and Pmax load (p < 0.05). The results of this study indicate that the use of instant feedback during jump-squat training in athletes was beneficial for improving multiple performance tasks over 6 weeks of training. Instant feedback is an important element of power training to maximize adaptations when training strength-trained athletes.